Penerapan Algoritma Sattolo Shuffle Dalam Sistem Distribusi Kupon Undian Digital Pada Platform E-Commerce - Surya Darma Nasution; Guidio Leonarde Ginting (Graha Mitra Edukasi, 2025)
The distribution of digital lottery coupons on e-commerce platforms requires a fair and efficient randomization mechanism. This study implements the Sattolo Shuffle algorithm as a digital coupon distribution mechanism with a case study of 20 coupons to 20 users. The Sattolo Shuffle algorithm is a modification of the Fisher-Yates Shuffle that produces cyclic permutations, where every element is guaranteed to move from its original position. The shuffling process was carried out through 19 iterations (n-1) and verified through fixed point analysis, permutation cycle tracking, and coupon distribution to users. Test results show 0 fixed points (100% elements moved), a single cycle covering all elements, and even coupon category distribution. Comparison with standard Fisher-Yates and Naive Shuffle confirms Sattolo Shuffle superiority in derangement guarantee, distribution fairness, and O(n) computational efficiency